Perceived Difficulties in TOEFL Listening: A Diagnostic Study of Indonesian EFL Learners at UNAI - Nelson Balisar Panjaitan (LPPM Universitas Advent Indonesia, 2026)
Indonesian EFL undergraduates at faith-based Universitas Advent Indonesia (UNAI) face persistent TOEFL listening challenges, yet institution-specific diagnostics remain scarce. This quantitative descriptive study surveyed 135 UNAI students with prior TOEFL exposure using a validated 40-item, 5-point Likert-scale questionnaire assessing perceived difficulties across six domains: vocabulary (M=3.22, moderate), speech rate (M=3.59, moderately high), accent variation (M=3.50, moderately high), distractors (M=3.43, moderately high), memory (M=3.49, moderate), and concentration (M=3.52, moderately high). Overall mean difficulty was 3.46 (moderately high), revealing processing constraints over lexical gaps. Key findings identified concentration (peak item M=4.01) as the most critical barrier—driven by anxiety and noise—followed closely by speech rate (up to M=3.88), memory (M=3.83), distractors (M=3.75), and accents (M=3.67). Vocabulary ranked lowest, suggesting top-down compensation mitigates lexical limits. This pattern underscores TOEFL listening as a multidimensional construct blending linguistic knowledge with cognitive load (working memory, processing speed), attentional control, and affective factors rather than vocabulary deficits alone. Implications advocate targeted interventions beyond rote vocabulary: rapid-speech training, diverse accent immersion, distractor recognition drills, note-taking systems, memory enhancement techniques, and anxiety management protocols. These strategies promise to elevate UNAI students' TOEFL competitiveness and listening proficiency in high-stakes academic contexts.